Comparing Onset of Biosimilar Versus Generic Competition in the United States. Issue 6 (17th August 2020) - Beall, Reed F.; Ronksley, Paul E.; Wick, James; Darrow, Jonathan J.; Sarpatwari, Ameet; Kesselheim, Aaron S.
Abstract : We sought to compare expected and observed biosimilar and generic entry dates among new drugs approved by the US Food and Drug Administration (FDA) between 2000 and 2012. We defined expected biosimilar and generic entry dates as the later of the expiration of the key patent term or statutory exclusivity (12 years for biologics, 5 years for small molecule drugs not indicated for a rare disease, and 7 years for small molecule drugs indicated for a rare disease; plus 6 months if a pediatric extension had been granted). For drugs with expected entry prior to 2019, we calculated the proportion with observed biosimilar or generic entry. The expected biosimilar entry dates were estimated to be a median of 12.3 years (interquartile range (IQR) 12.0–14.0, n  = 60) after FDA approval. The 12‐year biologic statutory exclusivity period comprised 98% of the median expected protection period. By contrast, expected generic entry was estimated to be a median of 12.2 years (IQR 8.4–14.0, n =268), or 7.2 years after the 5‐year small molecule statutory exclusivity (59% of the total expected market protection period). By 2019, observed biosimilar entry occurred in 12% of cases (3/25) and observed generic entry in 65% (101/155). We concluded that expected US market exclusivity periods are similar for biologic and small molecule drugs. Statutory exclusivity plays a more substantial role in market exclusivity protection for biologics. Biosimilar competition, currently lagging behind generic competition, will likely increase as the biosimilar market becomes established.